Gamification Elements in the Process of Ukrainian Language Training of Pedagogy Specialists - Humeniuk, Iryna (Journal of Vasyl Stefanyk Precarpathian National University, 2023)
The article studies the problem of using gamification elements in the process of training future preschool and primary school teachers on the example of the methodology of teaching Ukrainian Language for Professional Purposes. The necessity of improving the methodology of teaching the language to students of different age groups while taking into account the main educational trends and public demand has been substantiated. According to the goal, the essence of the "gamification" concept has been defined regarding the modern education sector. The peculiarities of using gamification, which have a great impact on the effectiveness of teaching students at pedagogical institutions of higher education, have been determined. It is emphasized that the growth of the number of game means in the methodology of teaching Ukrainian Language for Professional Purposes is not always directly proportional to the increase of success. Since gamification is impossible without using information and communications technology, consideration of the factor of appropriate technological support is necessary. The age factor manifests itself rather in the information and technological skills and abilities of certain age groups than the effectiveness of completed tasks on the condition of unhindered mastery of the technology. In the process of gamification, the element of novelty has a significant impact, as well as the temporal and motivational dependence of the interest of the performers on the duration or algorithmization of the tasks. The psychological factor is manifested through gender, which substantiates the inefficiency of using gamification with elements of competition or open ranking of results for female audience. In the context of training pedagogy specialists, the process of gamification during the study of a certain discipline has a dual purpose: increasing the motivation and therefore the effectiveness of training, formation of necessary competencies of future teachers; mastering completed gamified tasks as possible ways and means of teaching the Ukrainian language in future professional activity. Based on the analysis of the information space of the problem, a system of tasks with gamification elements has been developed and adapted to the content of the Ukrainian Language for Professional Purposes academic discipline.